Rescue Board : the untold story of America's efforts to save the Jews of Europe - Erbelding, Rebecca (Doubleday, 2018)
"America has long been criticized for refusing to give harbor to the Jews of Europe as Hitler and the Nazis closed in. Now a U.S. Holocaust Memorial Museum scholar tells the extraordinary story of the War Refugee Board, President Franklin D. Roosevelt's little-known effort late in the war to save the Jews who remained. In January 1944, a young Treasury lawyer named John Pehle accompanied his boss to a meeting with the president. For more than a decade, the Jews of Germany had sought refuge in the United States and had been stymied by Congress's harsh immigration policy. Now the State Department was refusing to authorize relief funds Pehle wanted to use to help Jews escape Nazi territory. At the meeting, Pehle made his best case...and prevailed. Within days, FDR created the War Refugee Board, empowering it to rescue the victims of Nazi persecution, and put John Pehle in charge. Over the next twenty months, Pehle pulled together a team of D.C. pencil pushers, international relief workers, pirates, diplomats, millionaires, confidence men, and rabble-rousers to run operations across four continents and a dozen countries. Together, they tricked the Nazis, forged identity papers, smuggled food into concentration camps, recruited spies, leaked news stories, negotiated ransoms, and funneled millions of dollars into Europe. They bought weapons for the French Resistance and ships to transport Romanian refugees to Palestine. Altogether, they saved tens of thousands of lives. In Rescue Board, U.S. Holocaust Memorial Museum scholar Rebecca Erbelding uses unrivaled access to archival materials and fresh interviews with survivors to tell the dramatic unknown story of America's last-ditch effort to save the Jews of Europe"...